ANALISIS FAKTOR RISIKO GANGGUAN MUSKULOSKELETAL PADA PEKERJA PENYAPU JALAN DI KOTA MATARAM - Wahyu Kurniawan; Agus Riyanto; Gurdani Yogisutanti (Poltekkes Kemenkes Semarang, 2026)
Street sweepers perform heavy, continuous work, potentially leading to musculoskeletal disorders. They are not aware of the center of gravity, early signs and symptoms of disorders, and appropriate treatment when experiencing disorders, which can reduce work productivity. This study aimed to analyze determinant factors associated with musculoskeletal disorders among street sweeper workers. This study employed a quantitative design with a cross-sectional approach. The study population consisted of all street sweeper workers in Mataram City, totaling 195 respondents, selected using a total sampling technique. Musculoskeletal disorders were assessed using the Nordic Body Map (NBM) questionnaire. A total of 63.6% of respondents experienced musculoskeletal disorders. Musculoskeletal disorders were associated with smoking habits (p = 0.0001), length of employment (p = 0.057), and repetitive work movements (p = 0.0001), whereas body mass index, working duration, working posture, workload, and psychosocial factors were not significantly associated (p > 0.05). Multivariate analysis indicated that smoking habits (p = 0.0001; Exp(B) = 4.643), length of employment (p = 0.004; Exp(B) = 0.935), and repetitive work movements (p = 0.0001; Exp(B) = 0.895) were significantly associated with musculoskeletal disorders. Smoking habits being the most dominant factor associated with musculoskeletal disorder.